If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 8 + -12x + 6 = 0 Reorder the terms: 8 + 6 + 5x + -12x = 0 Combine like terms: 8 + 6 = 14 14 + 5x + -12x = 0 Combine like terms: 5x + -12x = -7x 14 + -7x = 0 Solving 14 + -7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -7x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -7x = 0 + -14 -7x = 0 + -14 Combine like terms: 0 + -14 = -14 -7x = -14 Divide each side by '-7'. x = 2 Simplifying x = 2
| 6n+4=3n+12 | | -15+5z=2+1 | | 17r+8=42 | | -4c=-416 | | 14y+-94=816 | | -18+7x=-x^2 | | -4x^2+6x-(-2)=0 | | 10(-1.5)+10y=-100 | | m*14=175 | | 6t=#(t+4)+t | | 15+8y=3y | | 4x+7y=-80 | | 5p=100 | | 6q-4=-1 | | 8d-5=9d-8 | | W*2=97 | | -6x+2x-5x=0 | | 8d-5=9d-7 | | 0.07=50x | | 4*j=12.4 | | -3a(t+5)+(4t+2)=8 | | 3(x-6)=x*2 | | log[2](4x)+log[2](x-2)=5 | | 3-4+9=7 | | 5*h=105 | | 14-3*2= | | 4*3a+2(a+6b)= | | K*15=75 | | (6x+4)+(8x+6)=8(2x+1) | | 6(2d-d)=25 | | (5x-2)-(3x+1)= | | M+13.8=-4.5 |